A consistent energy-based cohesive zone model to simulate delamination between differently oriented plies. (15th February 2022) - Zani, Mathilde; Fanteria, Daniele; Catapano, Anita; Montemurro, Marco
Abstract: A consistent energy-based cohesive zone model to simulate the mode I delamination behaviour of Fully-Uncoupled Multi-Directional (FUMD) laminates is presented in this study. The proposed energy-based approach allows determining a more general constitutive response of the cohesive interface to better match the experimental results. The constitutive behaviour of the interface is implemented in a standard finite elements (FE) code by means of a user-defined subroutine. To perform the simulations, FE models of a Double Cantilever Beam (DCB) specimen are developed with standard and multidirectional interfaces. The results of the simulations are compared to the experimental ones in terms of force–displacement curves and crack front shape to assess the effectiveness of the proposed model. The comparison shows that the numerical simulations can closely replicate the opening delamination behaviour of DCB specimens during propagation and, in particular, they capture quite well the shape of the delamination fronts with some differences: numerical delamination fronts are characterised by a curvature lower than the one of the experimental counterparts, especially towards the specimen edges. Simulations carried out for different initial delamination lengths confirmed that the delamination changes its front shape at the very beginning of the propagation, then the front remains unaltered. The length of the transition zone for the shape of the delamination front has been found to be much lower than the specimen width.